Optimization of different auxin and cytokinin combination in nutrient medium for establishment of optimal in vitro multiple plantlet in Ficus carica L. cv Siyah Orak - Justin, Marianna; James Antony, Jessica Jeyanthi; Embu, Eldred; Subramaniam, Sreeramanan (Malaysian Society of Applied Biology, 2023)
Ficus carica Linnaeus is a flowering plant under the Moraceae family, usually propagated conventionally from cuttings due to the seeds being non-viable. However, this method is prone to diseases, and pests, time-consuming and space-intensive. Therefore, other methods are needed to overcome these issues. This study was conducted to induce callus and multiple shoots via plant tissue culture techniques enabling mass production of fig plants. Initially, leaf segments of Ficus carica L. cv Siyah Orak were cultured on different MS media strengths (¼, ½, ¾,1 MS) to induce callus. The highest callus means weight was observed on explant cultured in ¾ MS media (875±0.036). Callus was proliferated by subculturing explant into ¾ MS media supplemented with different concentrations of TDZ (0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0 mg/L). MS media (3/4) supplemented with 2.0 mg/L TDZ (920±0.03) shows the best result for callus proliferation. Callus induction using transverse and longitudinal thin cell layers from nodal segments cultured on different MS media strengths (¼, ½, ¾,1 MS) shows ¼ MS as the optimum media for both tTCL (100±0) and lTCL (96.7±0.15). Friable callus (%) was observed the highest on ½ MS (63.33±0.55) and ¼ MS (76.67±0.50) media for both tTCL and lTCL, respectively. As for the number of leaves produced, both tTCL (0.83±0.0.28) and lTCL (1.00±0.33) explant showed the best results in ¼ MS media. Apical buds produced the highest mean for both the number of leaves and length of the shoot on 1MS media supplemented with 2.0 mg/L BAP (3.5±0.20, 13.73±0.66), respectively. For root formation (%) and number of roots, both show the best results in media supplemented with 2.5 mg/L IAA (10±0.31, 0.83±0.50). It can be concluded that the best shoot growth performance was observed from apical bud cultured on 1MS media supplemented with 2.0 mg/L BAP+ 2.5 mg/L IAA.